Comparison of the effects of a low-protein diet with the effects of a converting enzyme inhibitor on the progression of renal insufficiency in hypertensive rats - Cervenka, L; Heller, J (Renal failure, 1996)
The beneficial effects of a low-protein diet vs. angiotensin-converting enzyme inhibitor (ACEI, enalapril) on the course of ablation nephropathy (5/6 nephrectomy, 5/6NX) were compared in a new strain of genetic hypertensive rats, the Prague hypertensive rat (PHR). Both maneuvers were followed by a significant drop in proteinuria (1.27 and 8.8 vs. 56.2 mg/24 hod, p < 0.001, low-protein diet vs. ACEI vs. untreated), plasma levels of creatinine (175.3 and 177.1 vs. 245.3 mumol/L, p < 0.001) and urea (7.95 and 13.51 vs. 37.6 mmol/L, p < 0.001). Endogenous creatinine clearance was higher after both low-protein diet and ACEI than without them (134.6 and 127.8 vs. 56.7 microL/min/100 g BW, p < 0.001). Both maneuvers had a similar beneficial effect: no additional amelioration was observed with a combination of both low-protein diet and ACEI. Compared to normotensive Wistar rats, the results were quite similar in PHR except the blood pressure values; hypertension had no substantial effect on the course of 5/6NX or on the beneficial action of both low-protein diet and ACEI.
Keywords: renální insuficience; kombinovaná terapie; Angiotensin-Converting Enzyme Inhibitors; Diet, Protein-Restricted; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; Disease Progression; Hypertension; inhibitory ACE; krysa rodu Rattus; Antihypertensive Agents; Enalapril; zvířata; časové faktory; Renal Insufficiency; enalapril; potkani inbrední SHR; hypertenze; Rats; progrese nemoci; Animals; Combined Modality Therapy; Nephrectomy; antihypertenziva; nízkoproteinová dieta; nefrektomie; Rats, Inbred SHR; Time Factors